Prediction of sugarcane quality parameters using visible-shortwave near infrared spectroradiometer - Mat Nawi, Nazmi; Kamal, Md Rowshon; Chen, Guangnan; Jensen, Troy (Elsevier, 2014)
This study was undertaken to explore the potential of spectroscopic method to predict sugarcane quality parameters by directly scanning the internode samples. Spectral data was collected from 125 internode using a visible-shortwave near infrared spectroradiometer (VNIRS). The spectral data was calibrated using Partial Least Square (PLS) method against the reference values of Brix, fibre content (FC) and moisture content (MC). The prediction results for Brix, FC and MC as represented by coefficient of determination (R2) were 0.88, 0.93 and 0.90,respectively. These results suggested that the spectroscopic method could be used to predict sugarcane quality parameters with good accuracy.